Leadership of community education: evidence from Indonesia - Somantri, Cecep (2021)
Literature and research on educational leadership and management have received increasing attention in the last three decades. However, out-of-school leadership and community education are two areas that remain under-researched, globally and in Indonesia. This study aims at gaining an understanding of the ways in which the leadership of community education is practiced in Indonesia. It examines the nature of leadership in Indonesian Community Learning Centres (CLCs). It further explores CLC organisational structure, the relationship of CLCs with the community, CLC networking and partnership strategies, curriculum development, and the methods employed by CLC leaders and teachers to engage with learners.